Virtual Reality exposure therapy for public speaking anxiety in routine care: a single-subject effectiveness trial - Lindner, Philip; Dagöö, Jesper; Hamilton, William; Miloff, Alexander; Andersson, Gerhard; Schill, Andreas; Carlbring, Per (Cognitive behaviour therapy, 2021)
Virtual Reality (VR) can be used as a therapeutic tool to conduct efficacious in-session exposure therapy by presenting virtual equivalents of phobic stimuli, yet past hardware restrictions hindered implementation in routine care and effectiveness studies. The current study examines the effectiveness of a VR-assisted treatment protocol for public speaking anxiety with demonstrated efficacy, this time in routine care, using affordable VR hardware. Participants (n = 23) were recruited via a private clinic and treated by one of four psychologists with only minimal VR-training. Using a single-subject design and dual-slope modeling (adjusting the treatment-onset slope for treatment effects), we found a significant, large decrease in self-rated public speaking anxiety following the primary three-hour session, similar in magnitude to the previous efficacy trial. Multilevel modeling of in-session process measures suggests that the protocol works as intended, by decreasing catastrophic belief expectancy and distress, and increasing perceived performance quality. Adherence to the online transition program that followed-encouraging in-vivo exposure-was relatively poor, yet symptoms decrease continued. No change was observed over the three-month follow-up period. We conclude that VR exposure therapy can be effective under routine care conditions and is an attractive approach for future, large-scale implementation and effectiveness trials.